Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1614/wt-d-12-00166.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coapplied Glyphosate, Pyrithiobac, Pendimethalin, orS-Metolachlor on Cotton Injury, Growth, and Yield

Abstract: Field studies were conducted in Louisiana and Mississippi in 2009 and 2010 to evaluate coapplications of glyphosate, pyrithiobac, and residual herbicides on growth and yield of glyphosate-resistant cotton. Treatments were a factorial arrangement of glyphosate (0 and 860 g ae ha−1), pyrithiobac (0 and 470 g ai ha−1), and two residual herbicides (pendimethalin [1,120 g ai ha−1],S-metolachlor [1,070 g ai ha−1], and no residual herbicide). Cotton injury was greatest 3 d after treatment (DAT) and decreased at each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Weed control programs aimed at managing herbicide-resistant weeds recommend the use of annual herbicide rotation and tank mixtures with multiple modes of action (Beckie et al 2006;Norsworthy et al 2012). Diversifying herbicide programs with the use of soil-applied residual PRE herbicides in conjunction with effective POST herbicides is critical for management of herbicideresistant weeds (Norsworthy et al 2012;Stephenson et al 2013). Previous researchers have reported variable levels of kochia control with PRE or POST herbicides.…”
mentioning
confidence: 99%
“…Weed control programs aimed at managing herbicide-resistant weeds recommend the use of annual herbicide rotation and tank mixtures with multiple modes of action (Beckie et al 2006;Norsworthy et al 2012). Diversifying herbicide programs with the use of soil-applied residual PRE herbicides in conjunction with effective POST herbicides is critical for management of herbicideresistant weeds (Norsworthy et al 2012;Stephenson et al 2013). Previous researchers have reported variable levels of kochia control with PRE or POST herbicides.…”
mentioning
confidence: 99%
“…There are known dose-dependent effects of other herbicides on various crops. Stephenson et al [26] found that S-metolachlor damaged cotton, while pendimethalin had no such effect. Smith [27] found that low-dose pendimethalin had no signi cant effect on the biomass of Basella alba.…”
Section: Resultsmentioning
confidence: 99%
“…Although higher levels of injury were present, and plant height was reduced, cotton lint yield was unaffected by herbicide application. Stephenson et al (2013) reported that applications of S-metolachlor at two-to three-leaf cotton reduced plant height (5%) and number of nodes (6%) at 21 DAA, although cotton yield was not affected.…”
Section: Plant Growth and Development Parametersmentioning
confidence: 99%